Serum Visfatin does not seem to be a Useful Marker to Guide Glucocorticoid Substitution in Adrenal Insufficiency - Fichna, Marta; Czarnywojtek, Agata; Sowińska, Anna; Gryczyńska, Maria; Gut, Paweł; Ruchała, Marek (Hormone and Metabolic Research, 2020)
Primary adrenal insufficiency (Addison’s disease, AD) requires lifelong steroid substitution. Excess exogenous glucocorticoids promote abdominal obesity, insulin-glucose imbalance, and hypertension. Reliable markers of the adequate glucocorticoid replacement are lacking. Visfatin is a pro-inflammatory adipokine, with enzymatic activity of nicotinamide phosphoribosyltransferase. It enhances leukocyte function and synthesis of tumour necrosis factor α (TNFα) and interleukin-6 (IL-6). Serum visfatin is elevated in autoimmunity, but also in obesity, insulin resistance, and metabolic syndrome. This study was aimed to investigate whether serum visfatin could guide the glucocorticoid substitution in AD. Biochemical analyses were performed in 96 patients with AD (mean age 43.3±14.9 years) and 91 controls (43.5±12.5 years). Visfatin level was significantly elevated in patients with AD compared to controls (p<0.0001). Higher circulating IL-6 was also detected among subjects with AD (p=0.006). In AD, visfatin level was positively correlated with IL-6 (p=0.014), TNFα (p=0.001), body mass (p=0.015), fasting insulin (p=0.001) and HOMA-IR (p=0.001). No relationship was noticed with daily hydrocortisone (p=0.096) and urinary free cortisol excretion (p=0.499). Only the correlations with IL-6 and fasting insulin survived multiple regression analysis (p=0.049 and p=0.005, respectively). Additionally, positive correlation between visfatin and autoantibodies to 21-hydroxylase was noted (p=0.005). In the control group serum visfatin was correlated with IL-6 (p=0.009) and TNFα (p=0.0002). The current study reveals elevated serum visfatin in autoimmune AD. Visfatin does not seem a useful marker of the glucocorticoid replacement, although it correlates with fasting insulin and pro-inflammatory molecules. Further functional analyses are warranted to elucidate the role of visfatin in autoimmunity.
Keywords: adrenal insufficiency; cytokine; glucocorticoid replacement; visfatin